ОСНОВНЫЕ ОРГАНИЗАЦИОННО-ПРАВОВЫЕ ПРОБЛЕМЫ ДОГОВОРА КОМПЛЕКСНОЙ ПРЕДПРИНИМАТЕЛЬСКОЙ ЛИЦЕНЗИИ В РЕСПУБЛИКЕ КАЗАХСТАН (Journal of actual problems of jurisprudence, 2019)
If we take into account all these problems, we will achieve high results as soon as possiblethe growth of the economy and the country as a whole, will undergo painless integration in the future withworld economic space